2021
DOI: 10.1155/2021/6663195
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Breast Cancer Screening among the Medical and General Population of the North Region of Cameroon

Abstract: Breast cancer has become a real public health problem in Cameroon, particularly in rural areas due to late diagnosis, resulting partly from the absence of national screening programs. This work is aimed at assessing breast cancer awareness in the North Region of Cameroon. Participants were selected in six health centers surrounding the rural area of Garoua, North Region, Cameroon, and administered a questionnaire aimed at assessing their awareness about breast cancer risk factors and screening. Out of the 475 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The sources of breast cancer screening messages reported in this study were similar to other studies done in Cameroon (13) and Kenya (14,15). The latter studies identi ed sources of information to be media, family/ friends, and health care providers.…”
Section: Discussionsupporting
confidence: 80%
“…The sources of breast cancer screening messages reported in this study were similar to other studies done in Cameroon (13) and Kenya (14,15). The latter studies identi ed sources of information to be media, family/ friends, and health care providers.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, studies conducted across Africa revealed that BC has often been associated with misfortune, witchcraft, or as a result of divine punishment, supernatural or spiritual problems [ 8 , 17 ]. However, lump in the breast, changes in the shape, appearance of the breast, and pain were the most common symptoms listed by the women as reported in previous studies [ 13 , 14 , 18 , 19 ]. In Africa, and particularly in the northern part of Cameroon, people mostly associate the severity of diseases, including breast cancer, with the onset of pain.…”
Section: Discussionmentioning
confidence: 65%
“…Consequently, patients usually consult a physician when ulceration appears on the breast or the lumps grow and/or become painful, thus contributing to a late diagnosis of breast cancer. Unfortunately, since these signs usually occur at late stages of the disease, they are associated with a very poor prognosis [ 14 , [19] , [20] , [21] , [22] , [23] , [24] ,].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common methods for detecting breast cancer in its early stages are breast self-examination (BSE), clinical breast examination (CBE) and mammography. Mammography screening is expensive, requires a signi cant amount of nancial and human resources, and is thus not feasible in developing nations (11,12). BSE is a means for a woman to examine her breast for changes such as discharge, lumps, or thickenings, as well as the early diagnosis of breast lumps.…”
Section: Introductionmentioning
confidence: 99%